Ladrang Siyem: The Royal Anthem of Thailand, in Javanese Gamelan Version - Jamnongsarn, Surasak; Detkrut, Phunchita; Wangsaptawee, Yotin (Resital: Jurnal Seni Pertunjukan, 2023)
Ladrang Siyem: The Royal Anthem of Thailand, in Javanese Gamelan Version. During 19th century, Thailand modernized by associating itself with the "West" or Westernization; consequently, musical concepts from the West were implemented. Sansoen Phra Barami, also known as the Thailand Royal Anthem, is a musical composition composed to pay tribute to the King of Thailand. Therefore, the Western musical style was utilized in the composition. The Thai people should examine Java's prosperity in the areas of transportation, postal and telegraph, railways, military, and irrigation, in addition to European colonial policies and governance styles toward Asian nations. Through the Netherlands, the relationship between Thailand and Java was revealed during the three visits of Thai King Chulalongkorn in 1870, 1896, and 1901, as well as King Prajadhipok in 1929. An item that was performed in homage to His Majesty King Prajadhipok, King Rama VII of Thailand, who arrived at Surakarta palace in 1929 accompanied by the Queen, is Ladrang Siyem, which is the Javanese rendition of the Thai Royal Anthem. This item is mentioned in an archive titled Serat Saking Gotek or Wedhapradangga. The Javanese musicians at the Surakarta Palace adapted the gamelan piece known as "Sansoen Phra Barami" to become known as "Ladrang Siyem." An unmistakable illustration of the manner in which crypto-colonialism is projected through music is provided by the occurrence. In other words, the text takes into consideration political movements that occurred in Southeast Asia during the time of the colonial era.